2013
DOI: 10.1371/journal.pone.0067744
|View full text |Cite
|
Sign up to set email alerts
|

Towards Clinical Molecular Diagnosis of Inherited Cardiac Conditions: A Comparison of Bench-Top Genome DNA Sequencers

Abstract: BackgroundMolecular genetic testing is recommended for diagnosis of inherited cardiac disease, to guide prognosis and treatment, but access is often limited by cost and availability. Recently introduced high-throughput bench-top DNA sequencing platforms have the potential to overcome these limitations.Methodology/Principal FindingsWe evaluated two next-generation sequencing (NGS) platforms for molecular diagnostics. The protein-coding regions of six genes associated with inherited arrhythmia syndromes were amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 34 publications
3
49
0
1
Order By: Relevance
“…The average GC content in these amplicons was 79.1%. As other reports have confirmed [5], overly high GC content influences the efficiency of amplification. In cases in which Ion Torrent PGM is unable to identify the pathogenic mutation, there is still a need to use other methods to make up for the challenges of sequencing high-GC content segments.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The average GC content in these amplicons was 79.1%. As other reports have confirmed [5], overly high GC content influences the efficiency of amplification. In cases in which Ion Torrent PGM is unable to identify the pathogenic mutation, there is still a need to use other methods to make up for the challenges of sequencing high-GC content segments.…”
Section: Discussionsupporting
confidence: 52%
“…It has already been adapted for clinical molecular diagnosis, from specific genes such as CFTR [3], BRCA1, and BRCA2 [4] to disease-causing gene panels such as inherited arrhythmia syndromes [5], long QT syndrome [6], and cardiomyopathies [7]. In this study, we aimed to construct and evaluate the efficiency of a fast and comprehensive assay based on a custom AmpliSeq™ panel and the Ion Torrent PGM sequencer for the detection of mutations in HPArelated genes (PAH, PTS, QDPR, GCH1, and PCBD1).…”
Section: Introductionmentioning
confidence: 99%
“…The platforms leverage different sequencing technologies: Illumina utilizes sequencing-by-synthesis, measuring the signal as fluorescently-tagged nucleotides bind [131], while Ion employs semiconductor sequencing, in which the shift in pH caused by the release of hydrogen ions during DNA extension is measured [132]. While each platform and associated sequencing method has its own advantages and disadvantages, it has been repeatedly demonstrated that performance is relatively comparable for similar applications [133,134], and they uniformly allow for high throughput and multiplexing, low sequencing costs, and low error rates [130]. When comparing these two NGS platforms against each other, the main differences are the turnaround time and upfront cost; the elimination of optics in Ion semiconductor sequencing has allowed for a faster runtime and lower upfront cost than Illumina, but Illumina ultimately offers a lower cost per base pair [133,134].…”
Section: Sequencing: the Next And The Next-next Generationmentioning
confidence: 99%
“…ent in the raw data but could not be called except with settings that also generated many additional false-positive calls (23 ), we conclude that the false-negative detection rate is largely due to suboptimal data analysis, a problem that might be solved by testing or developing alternative data software tools. Notwithstanding, it might be worthwhile to test alternative NGS-based sequencing machines such as the Illumina MiSeq (19,20,24 ) to further im- prove performance, because the approach we used here is not restricted to ISS. In particular, the use of alternative platforms could reduce the number of false-positive variants that occur mainly in homopolymer stretches, which is an inherent weakness related to the principle of sequencing by synthesis (25 ).…”
Section: Performance Of Issmentioning
confidence: 99%